From Biodeterioration to Creativity - Rodrigues, Alexandra (2022)
A.Z.M. was supported by the Ramon y Cajal contract RYC2019-026885 from the Spanish Ministry of Science and Innovation (MCIN). S.G.-P. was supported by the intramural project PIE_20214AT021 from the Spanish National Research Council (CSIC). Publisher Copyright: © 2022 by the authors.